The rationalization of personal protective equipment usage and the solution of its limitation during COVID-19 era - Irene Ratridewi; Saptadi Yuliarto (Medical Faculty of Brawijaya University, Indonesia, 2022)
Covid-19 pandemic is a global burden health problem caused by Coronavirus. The disease can be transmitted swiftly by droplets after sneezing, coughing, or holding stuff (droplet contaminated). The contagion is eased by bad habit like does not wash hand after touching others or stuff. To date, data says that The Covid-19 morbidity rate is still highest in a densely populated place. Even though several mechanisms in the community have been done to prevent the spreading of this disease, but the spread is still relatively high and needs medical treatment intervention in the health care system especially in the hospital.1 Moreover, the daily hospital treatment of Covid-19 patients’ needs appropriate personal protective equipment (PPE) to protect and to minimalize the risk of infection to health workers.